2006
DOI: 10.1111/j.1538-7836.2006.01856.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia and low B vitamin levels are independently associated with venous thromboembolism: results from the EDITH study: a hospital‐based case–control study

Abstract: Summary.  Background: Moderate hyperhomocysteinemia and B vitamins deficiency are thought to be risk factors for venous thromboembolism (VTE). The causality and independence of those associations are still questioned. Methods: We measured fasting serum total homocysteine, folates, and vitamin B12 levels as well as 5,10‐methylenetetrahydrofolate reductase (MTHFR) C677T genotypes in 467 patients hospitalized with a first well‐documented deep vein thrombosis and/or pulmonary embolism not related to a major acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
4
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 18 publications
0
48
4
3
Order By: Relevance
“…This level favorably compares with the results of our previous case-control study which found an association between PLP <21.7 nmol/L and an increased risk of first venous thrombosis. 8 Compared with patients with PLP ≥68.1 nmol/L, recurrence risk was almost twice as high among patients with PLP ≤23.3 nmol/L, and increase was independent of potential confounders including hyperhomocysteinemia (RR 1.72, 95% CI 1.00-3.00). Levels of vitamin B12 and folate were not measured and, therefore, the …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This level favorably compares with the results of our previous case-control study which found an association between PLP <21.7 nmol/L and an increased risk of first venous thrombosis. 8 Compared with patients with PLP ≥68.1 nmol/L, recurrence risk was almost twice as high among patients with PLP ≤23.3 nmol/L, and increase was independent of potential confounders including hyperhomocysteinemia (RR 1.72, 95% CI 1.00-3.00). Levels of vitamin B12 and folate were not measured and, therefore, the …”
Section: Resultsmentioning
confidence: 99%
“…However, in our previous study, levels of folate, vitamin B12 and B6 were measured, and a homocysteine-independent association with the risk of first DVT was only found for low vitamin B6. 8 Cumulative probability of recurrent VTE after four years was 22.3% (95% CI, 13.5%-31.1%) among patients with PLP ≤23.3 nmol/L and 14.4% (95% CI 11.5%-17.4%) among patients with higher levels (p=0.02, Figure 1). After adjustment for confounders including tHcy, RR of recurrence was 1.78 (95% CI 1.01-3.14) among patients with PLP ≤23.3 nmol/L compared with patients with higher levels.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Briefly, all patients ≥18 years hospitalized with a well-documented symptomatic VTE, were eligible for enrolment. For this report, we retained only outpatients, i.e.…”
Section: 2mentioning
confidence: 99%
“…In the study conducted by Oger et al (10), vitamin B12 deficiency was stated to be a risk factor for venous thromboembolism. In our patient, the increased level of homocysteine appeared to be associated with B12 deficiency.…”
Section: Discussionmentioning
confidence: 98%